(untitled) (Journal of Nepal Geological Society, 1992)
Small bodies of volcanite are recorded in the Lower Siwalik Formation in central Nepal. Petrological and geochemical studies of these rocks confined that they are basaltic in composition and possibly formed from the alkaline basaltic magma. Occurrence of these rocks within the Lower Siwalik Formation indicate a late Tertiary volcanic activity in this region.